Institutional arrangements to make public spending responsive to the poor—(where) have they worked? Review of the evidence on four major intervention types - Mogues, Tewodaj; Erman, Alvina (International Food Policy Research Institute, 2016)
There has been some recognition in the development community that building technical capacity of public service providers and increasing resources is not enough to bring about development outcomes. Researchers and practitioners are increasingly appreciating that accounting for the stated needs of communities supports the process of pro-poor public resource allocation. We examine four institutional arrangements that explicitly endeavor to make public spending responsive to the needs of the poor by moving decision-making procedures closer to the population—participatory budgeting, community-driven development (CDD) programs, decentralization, and delegated targeting of transfers. Using the existing literature, we compare experiences across the four arrangements and countries. Regarding responsiveness to needs of the poor, evidence is cautiously optimistic for participatory budgeting, CDD, and decentralization. As for delegating the targeting of transfers to subnational authorities and communities, evidence suggests that the effect may be regressive. However, there are important mediating effects of public spending responsiveness under the various institutional arrangements. Local elite capture is a key factor dampening pro-poor spending where either exogenous circumstances such as prevailing inequality, or inadequate program design, enable capture to materialize. Politics is an important determinant of the success of these arrangements.